Transjugular intrahepatic portosystemic shunt (TIPS) - Šurlan, Miloš (Radiology and oncology (Ljubljana), 2000)
Background. A clear presentation of TIPS indications and contraindications, which can be divided into absolute and relative, is given. Absolute indications are fresh and renewed bleeding of varices and inveterate ascites. Relative indications, on the other hand, are splenomegaly with hypersplenism, Budd-Chiari syndrome, liver transplantation and hepatorenal syndrome. Absolutecontraindications are severe liver dysfunction and right heart failure, while the relative ones polycystic liver degeneration, neoplasm, obstruction of the portal vein and severe local and systemic infection. Beforethe TIPS procedure, the level of dysfunction of the liver, right heart and kidneys is determined. Biochemical and blood tests, including a blood coagulation test, are made, the ammonia level in the serum is determined and possible obstructions/strictures of the portal vein are checked. A detailed description of the procedure, a care for patient and a operative monitoring are given. The success rate of the procedure is between 93% and 100% and the mortality rate within 30 days because TIPS is between 1% and 3%. The hemorrhage is stopped in 95% to 100%, the ascites is improved in 87% to 92% and the kidney function in 81%. In case of hypersplenism the thrombocytopenia is improved in 75% and leucopenia in 50% of patients. There are relatively fewcomplications during the procedure. Postoperative complications are more frequent due to stricture and obstruction of the shunt. After a two-year treatment the shunt is passable in 50% of patients. Thus, in a group of 29 patients, who were treated in the period of four years with an average monitoring period of two years, 22 patients (75,9%) are still alive and only 7died (24,1%). Six of dead patients suffered from alcoholic cirrhosis of the liver. In two cases the cause of death was not related to the TIPS and the cirrhosis of the liver. (Abstract truncated at 2000 characters).
Keywords: bolezni; Esophageal and gastric varices; gastroenterologija; Hepatic encephalopathy; Hepatomegaly; Hepatorenal syndrome; Intraoperative complications; jetra; Liver transplantation; ožilje; Patient selection; Portasystemic shunt, transjugular intrahepatic; Splenomegaly; TIPS; Treatment outcome; varice; zdravljenje